2021
DOI: 10.1016/j.jaci.2020.02.040
|View full text |Cite
|
Sign up to set email alerts
|

The sputum microbiome, airway inflammation, and mortality in chronic obstructive pulmonary disease

Abstract: Microbiome, Airway Inflammation and Mortality in COPD n=253 n=96 n=135Background: The sputum microbiome has a potential role in disease phenotyping and risk stratification in chronic obstructive pulmonary disease (COPD), but few large longitudinal cohort studies exist. Objective: Our aim was to investigate the COPD sputum microbiome and its association with inflammatory phenotypes and mortality. Methods: 16S ribosomal RNA gene sequencing was performed on sputum from 253 clinically stable COPD patients (4-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
123
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 34 publications
13
123
2
Order By: Relevance
“…There was an overall decreased alpha diversity (Shannon index) and non-significantly increased relative abundance of Haemophilus in patients with increased severity measured using both spirometry-based GOLD I-IV and new GOLD A-D classification scheme based on exacerbation frequency, CAT and mMRC scores [ Global Initiative for Chronic Obstructive Lung Disease (GOLD), 2019 ], consistent with previous findings ( Mayhew et al, 2018 ; Dicker et al, 2020 ) ( Supplementary Figures S4A,B ). No species-level taxa reached statistical significance in association with GOLD classification, CAT or mMRC scores (FDR P < 0.05).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…There was an overall decreased alpha diversity (Shannon index) and non-significantly increased relative abundance of Haemophilus in patients with increased severity measured using both spirometry-based GOLD I-IV and new GOLD A-D classification scheme based on exacerbation frequency, CAT and mMRC scores [ Global Initiative for Chronic Obstructive Lung Disease (GOLD), 2019 ], consistent with previous findings ( Mayhew et al, 2018 ; Dicker et al, 2020 ) ( Supplementary Figures S4A,B ). No species-level taxa reached statistical significance in association with GOLD classification, CAT or mMRC scores (FDR P < 0.05).…”
Section: Resultssupporting
confidence: 87%
“…Nevertheless, both our results (increased Ralstonia mannitolilytica in frequent exacerbators) and those of Leitao Filho et al supported the notion that identification of rare opportunistic pathogens may be associated with worse clinical outcome and prognosis of COPD patients. A recent study by Dicker et al showed that Haemophilus dominance at COPD clinical stability was linked to increased severity, frequent exacerbations and increased mortality ( Dicker et al, 2020 ). This is also consistent with our finding that increased relative abundance of Haemophilus , in particular H. influenzae species, was observed in patients with enhanced GOLD status.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the presence of NTHi can be associated with acute exacerbation episodes in CF [15]. Similar observations have been made in COPD patients, although in this case the NTHi infection was also associated with a worse clinical prognosis [16,17]. However, there are no observations on the effect of chronic NTHi infection in the progression of CF chronic airway disease, due to the presence of several clinical and microbiological cofounding factors, such as concomitant infections [15,19] and lack of available human cohorts.…”
Section: Introductionsupporting
confidence: 79%
“…45 Increased abundance of Haemophilus, Moraxella and Pseudomonas are described in COPD FE while non-FEs appear to associate with increased Actinomyces. 12,14,17,46 The stability of the COPD microbiome through longitudinal assessment remains inconsistent, with high variability reported in the AERIS study as compared to COPDMAP which found lower variability of beta-diversity in FE. 14,20 During AECOPD, a decreased alpha diversity associates with higher mortality and abundance of Staphylococcus, however, an absence of Veillonella is also a poor prognostic indicator.…”
Section: The Microbiome and Clinical Outcomes In Copdmentioning
confidence: 99%
“…13 In addition, diversity is further reduced as disease progresses, and is also reported during acute exacerbations (AECOPD). [13][14][15][16][17] The dominant microbial phyla in stable COPD include Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria while predominant genera include Haemophilus, Moraxella, Streptococcus, Veillonella, Pseudomonas and Prevotella. 2,16,18 Important microbial alteration occurs with COPD treatments, including during and following AECOPD.…”
mentioning
confidence: 99%